High Prevalence of Long-COVID Among Kidney Transplant Recipients: A Longitudinal Cohort Study - Amorim, Carlos Eduardo Neves; Gomes, Vinicius Lafico Teixeira; Cristelli, Marina Pontello; Viana, Laila Almeida; de Luca Correa, Hugo; Lima, Gierisson Brenno Borges; de Sousa Silva, Flaviana Santos; de Castro Lima, Gabriel Santos; Rosa, Thiago Dos Santos; Nakamura, Monica Rika; Quintino, Priscilla Monteiro; Tedesco-Silva, Helio; et al. (Transplantation, 2022)
Kidney transplant recipients are at a higher risk to develop more severe clinical forms of coronavirus disease 2019 (COVID-19), perhaps increasing the risk of presenting its long-term clinical complications, labeled as Long-COVID. This single-center, observational, prospective study included adult kidney transplant recipients with COVID-19 confirmed by reverse transcription polymerase chain reaction between March 20, 2020, and May 31, 2021, who were alive and with functioning graft 3 mo after the onset of symptoms. The prevalence of Long-COVID was investigated by a phone survey using a structured questionnaire of organic symptoms. Adjusted multivariable logistic regression models were used to investigate independent risk factors. Of 1741 patients who developed COVID-19, 465 died, and 37 returned to dialysis. Of the 1239 eligible patients, 780 (63%) answered the survey during the window period. The mean age was 48 ± 12 y, 41% were women, and the mean time from transplantation was 8 ± 6 y. During acute illness, 45% needed hospitalization. Long-COVID was identified in 214 (27%) of the subjects, with body aches being the most prevalent symptom (44%). Of 233 who provided working status, 17% did not return to work within 3 mo. No baseline characteristics or infection-related variables predicted Long-COVID; actually, the number of symptoms in the acute illness was the only independent risk factor identified (hazard ratio, 1.12; 95% confidence interval, 1.02-1.22). In this cohort of kidney transplant recipients, Long-COVID was prevalent and associated with a reduced return to work. The burden of acute phase symptoms was the only risk factor associated with Long-COVID.